4
$\begingroup$

This is what I did for:

$$\lim \limits_{x \to 0} \space \cot{x}-{1 \over x}$$

  1. Check form: $\infty - \infty$.
  2. Rearrange it to be a quotient: $$\begin{align} \\ & =\lim \limits_{x \to 0} \space {\cos{x} \over \sin{x}}-{1 \over x} \\ &\\ & =\lim \limits_{x \to 0} \space {x\cos{x} - \sin{x} \over x\sin{x}} \\ \end{align}$$
  3. Check form: $0 \over 0$
  4. Apply L'Hospital's Rule: $$ = \lim \limits_{x \to 0} \space {(-x\sin{x} + \cos{x}) - \cos{x} \over (x\cos{x} + \sin{x})} $$
  5. Check form: $0 \over 0$.
  6. Apply L'Hospital's Rule Again: $$ = \lim \limits_{x \to 0} \space {((-x\cos{x} -\sin{x}) +\sin{x}) -\sin{x} \over (-x\sin{x} + \cos{x}) + \cos{x}} $$
  7. Check form: $0\over2$.

Therefore:

$$\lim \limits_{x \to 0} \space \cot{x}-{1 \over x} = 0$$

This works, but seems that apply the rule twice made things really messy. Was there a simplification step that I missed along that way that would have made this easier to deal with (other than removing the parenthesis that I put in while using the power rule)?

$\endgroup$
5
$\begingroup$

You did indeed miss a simplification:

$$\lim \limits_{x \to 0} \space {(-x\sin{x} + \cos{x}) - \cos{x} \over (x\cos{x} + \sin{x})}=\lim \limits_{x \to 0} \space {-x\sin{x}\over (x\cos{x} + \sin{x})}$$

It's not a lot simpler, but it is simpler.

$\endgroup$
0
$\begingroup$

Speaking of simplicity, often by L'Hospital rule can be applied in combination with so-called remarkable limits. If this exercise can do so: $$\lim \limits_{x \to 0}( \cot{x}-{1 \over x})=\lim \limits_{x \to 0} \frac{x\cos x-\sin x}{x\sin x} = \lim \limits_{x \to 0} \frac{x\cos x-\sin x}{x^2}\cdot\lim \limits_{x \to 0}\frac{x}{\sin x}=$$$$=\lim \limits_{x \to 0} \frac{x\cos x-\sin x}{x^2} = \lim \limits_{x \to 0}\frac{\cos x-x\sin x- \cos x}{2x}= \lim \limits_{x \to 0}\frac{-x\sin x}{2x}=0.$$

Simplification is more obvious in the case of the more complicated example: $$\lim \limits_{x \to 0}( \cot^2 x-{1 \over x^2}) = \lim \limits_{x \to 0} \frac{x^2\cos^2 x-\sin^2 x}{x^2\sin^2 x} = \lim \limits_{x \to 0} \frac{x\cos x+\sin x}{x}\cdot\lim \limits_{x \to 0} \frac{x\cos x-\sin x}{x^3} \cdot\lim \limits_{x \to 0}\frac{x^2}{\sin^2 x}=\lim \limits_{x \to 0} (\cos x +\frac{\sin x}{x})\cdot\lim \limits_{x \to 0} \frac{x\cos x-\sin x}{x^3} = 2 \cdot \lim \limits_{x \to 0}\frac{\cos x-x\sin x- \cos x}{3x^2}= $$$$=-\frac{2}{3} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.